George Santayana correspondence and poem - Santayana, George, 1863-1952.
ALS (1937 June 1) written by Santayana to Richard Cheney relating to the game of chess; ALS (1939 June 10) from Santayana to Joseph Auslander enclosing a manuscript copy of Santayana's poem, At Arles; and TLS (1951 December 10) from Santayana to Donald C. Holmes, chief, Library of Congress Photoduplication Service, requesting that copies of the Auslander letter and poem be sent to Santayana's biographer, Bruno Lind.
Poet, philosopher, and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Auslander, Joseph, -- 1897-1965 -- Correspondence; Cheney, Richard, -- 1908- -- Correspondence; Holmes, Donald C. -- 1911- -- Correspondence; Lind, Bruno, -- 1909-; Chess; Arles (France) -- Poetry; Educators; Philosophers; Poets